Arsenic - Analytical and Toxicological Studies 2018
DOI: 10.5772/intechopen.74758
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Arsenic-Induced Toxicity with Special Emphasis on Arsenic-Binding Proteins

Abstract: The importance of different arsenic forms in public health is well recognized owing to its distinct physical characteristics and toxicity. Chronic arsenic exposure has left a trail of disastrous health consequences around the world. However, the mechanisms behind the toxicity and the consequential diseases occurring after acute or chronic exposure to arsenic are not well understood. The toxicity of trivalent arsenic primarily occurs due to its interaction with cysteine residues in proteins. Arsenic binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…As binding to plant cells may lead to protein folding or conformational changes. The proteins that bind to As are transcription factors, signalling proteins, metabolic enzymes, and certain structural proteins (Hussain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As binding to plant cells may lead to protein folding or conformational changes. The proteins that bind to As are transcription factors, signalling proteins, metabolic enzymes, and certain structural proteins (Hussain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al found a relation between exposure to arsenic and chronic kidney disease in Taiwan [9]. According to recent reports the arsenite toxicity is due to its interaction to cysteine residues in proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…It could be deduced that the bioactive compounds such as benzofuran 2,3 dihydro, hexadecaboic acid, cis-vaccenic acid and oleic acid present in the C. afer leaves hexane fraction might be responsible for the hepatoprotective effect [21]. Molecularly, arsenite is known to induce tissue toxicity through generation of oxidative stressors and cellular signals that result into the binding of arsenite to thiol groups of macromolecules with the subsequent propa gation of deleterious chemical species and apoptosis [28,29]. C. afer hexane leaf fraction has been shown to possess antioxidant and antiinflammatory property against reactive oxygen species (ROS) and proinflammatory mediators [19].…”
Section: Resultsmentioning
confidence: 99%